Work System Design in Macroergonomics: A Case Study Related to Prioritization of Major Sociotechnical System Components by Using the Fuzzy Analytic Network Process - (:unkn) unknown (WILEY, 2011)
The primary lesson for a company in an industrially developing country that desires to build its competitive capabilities is that investing and focusing solely on the technical side of the work system results in disruptive technological and organizational change. The managers should take into account THE broader prerequisites and be aware of the potential pitfalls of work system incompatibilities. Past experiences indicate that, to be successful, the work system design has to match certain requirements of major sociotechnical systems. Thus the matching process has to consider multiple criteria and the opinions of several managers. This work attempts briefly to identify factors affecting the success of work system design to reduce the potential for incompatibilities with respect to macroergonomics and to optimize the decision process of managers. The objective of the presented decision model in this article, based on the fuzzy analytic network process, determines the global weights (highest degree of importance) for different sociotechnical subsystem components/elements and examines the critical factors and benefits that affect the successful application of macroergonomic work system designs from a manager's point of view. (C) 2010 Wiley Periodicals, Inc.
Keywords: Macroergonomics; Work system design; Fuzzy ANP; QUALITY; ISSUES